PENGARUH ISTIGHOSAH TERHADAP PENGENDALIAN EMOSI JAMA’AH MAJELIS TA’LIM MIFTAHUL HUDA DESA POJOK KECAMATAN PONGGOK KABUPATEN BLITAR - Haryanti, Nik; Rohmah, Liatul; Rachmawati, Danar Nanda (Jurnal Ilmiah Sosiologi Agama (JISA), 2024)
This study aims to analyze the influence of istighosah on emotional control of Jama'ah Majelis Ta'lim Miftahul Huda, Corner Village, Ponggok District, Blitar Regency. The research method used is a quantitative research method used to examine certain populations or samples, data collection using research instruments, quantitative / statistical data analysis with the aim of testing hypotheses that have been set. The approach used in this study is an associative approach, which is research that aims to determine the relationship between two or more variables Data analysis techniques used simple linear regression. The results of this study show that there is a positive and significant influence between istighosah on emotional control of Jama'ah Majelis Ta'lim Miftahul Huda, Desa Corner, Ponggok District, Blitar Regency, which means that the higher the istighosah activities in the congregation, the higher the emotional control of the Jama'ah Majlis Ta'lim.